The Value of Telemedicine for the Follow-up of Patients with New Onset Type 1 Diabetes Mellitus During COVID-19 Pandemic in Turkey: A Report of Eight Cases - Ferda Evin; Eren Er; Aysun Ata; Arzu Jalilova; Günay Demir; Yasemin Atik Altınok; Samim Özen; Şükran Darcan; Damla Gökşen (Galenos Yayincilik, 2021)
The current Coronavirus disease-2019 (COVID-19) pandemic has forced health care teams to look for alternative approaches to manage a great number of children with diabetes, not only in rural but also in urban locations. The aim was to assess the provision of information about follow-up of new-onset pediatric type 1 diabetes (T1D) patients, and to investigate the integration of telemedicine into routine clinical care in the long term. The changes in coefficient of variation (CV), standard deviation and percentages of time in range (TIR), time below range (TBR) and time above range were evaluated in eight children with new-onset T1D, diagnosed during the COVID-19 pandemic. The study period was two-months of follow-up using a telemedicine system. Median follow-up time was 51 (24-66) days. Two of the patients were using low glucose suspend system and six were on multiple daily injection therapy. Target TIR values were achieved in seven patients in the last televisit and, in line with recent guidelines, a TBR <70 mg/dL (<3.9 mmol/L) (level 1 hypoglycemia) of <4% and a TBR <54 mg/dL (<3.0 mmol/L) (level 2 hypoglycemia) of <1% were achieved in all patients. Seven patients achieved a CV of <36% at their last televisit. Telemedicine as an alternative follow-up tool during unusual circumstances such pandemics, even in countries where it is not routinely used, could be beneficial to achieve optimum glycemic control in patients with new-onset T1D.